Idiopathic atrial fibrillation patients rapidly outgrow their low thromboembolic risk: a 10-year follow-up study - Weijs, B. (Neth Heart J, 2019)
BACKGROUND: Healthy atrial fibrillation (AF) patients will eventually outgrow their low thromboembolic risk. The purpose of this study is to compare the development of cardiovascular disease in healthy AF patients as compared to healthy sinus rhythm patients and to assess appropriate anticoagulation treatment. METHODS: Forty-one idiopathic paroxysmal AF patients (56 ± 10 years, 66% male) were compared with 45 healthy sinus rhythm patients. Patients were free of hypertension, antihypertensive and antiarrhythmic drugs, diabetes, congestive heart failure, coronary artery or peripheral vascular disease, previous stroke, thyroid, pulmonary and renal disease, and structural abnormalities on echocardiography. RESULTS: Baseline characteristics and echocardiographic parameters were the same in both groups. During 10.7 ± 1.6 years, cardiovascular disease and all-cause death developed significantly more often in AF patients as compared to controls (63% vs 31%, log rank p < 0.001). Even after the initial 5 years of follow-up, survival curves show divergent patterns (log rank p = 0.006). Mean duration to reach a CHA(2)DS(2)-VASc score > 1 among AF patients was 5.1 ± 3.0 years. Five of 24 (21%) patients with CHA(2)DS(2)-VASc > 1 did not receive oral anticoagulation therapy at follow-up. Mean duration of over- or undertreatment with oral anticoagulation in patients with CHA(2)DS(2)-VASc > 1 was 5 ± 3.0 years. CONCLUSION: The majority of recently diagnosed healthy AF patients develop cardiovascular diseases with a consequent change in thromboembolic risk profile within a short time frame. A comprehensive follow-up of this patient category is necessary to avoid over- and undertreatment with anticoagulants.